Correction to: An unusual cause of infant’s stridor – congenital laryngocele - Andrea Ambrus; Balázs Sztanó; Miklós Szabó; Béla Vasas; István Sziller; László Rovó (Journal of Otolaryngology - Head and Neck Surgery, 2020)
An amendment to this paper has been published and can be accessed via the original article.